Current advancements of and future developments for fourth party logistics in a digital future - Hans-Joachim Schramm; Carolin Nicole Czaja; Michael Dittrich; Matthias Mentschel (Logistics, 2019)
This paper aims to analyze the potential future of the 4PL concept based on expert opinions with special regard to the influence of digitalization coming with a disruptive trans-formation of supply chains. Service arrangements, provider capabilities and benefits resulting from a 4PL partnership are compared in current and future configurations. The research follows an explorative mixed methods approach with semi-structured interviews followed by an expert panel. This builds a basis for an online survey questionnaire to inquire on important future aspects for the 4PL concept by a sample of respondents from multinational companies. Our results show a clear trend away from simply organizing transportation and logistics activities towards the provision of an IT platform as well as further value-added service activities such as planning, analytics and monitoring. Along with this, IT capabilities appear to be an important differentiator for 4PL providers in the future. Moreover, relationships between 4PL providers and their clients become closer and more strategic, which leads to a customer valuing not only direct cost reductions but rather improvements resulting from optimized operations through superior analysis and planning functions.
Keywords: 650; digitalization; fourth-party logistics (4PL); IT capabilities